A 6-BIT HIGH SPEED ANALOG TO DIGITAL CONVERTER USING INTEL 8085 MICROPROCESSOR - H S, Bhaskar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Architecture to simplify the circuit implementation of the analog-to-digital (A/D) converter is proposed, the approach partitions input range into N-quantization cells, separated by N-1 boundary points. The Microprocessor decides with in which cell the input sample lies. The successive approximation technique translates input sample to digital domain. This makes the quantization feasible with much higher speed than with conventional successive approximation technique. Results of 8 bit prototype is presented.